Eco-hydrology of Pollardstown Fen, Co. Kildare, Ireland - Kuczynska, Anna Malgorzata (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2008)
Calcareous fens are wetlands that accumulate peat and have alkaline groundwater as their dominant hydrologic input. This combination of environmental characteristics produces an unusual type of habitat and a large number of rare and regionally important plant and invertebrate species are found within these fens. Groundwater discharge to a fen is the critical factor controlling the ecology of a fen. An understanding of eco-hydrological links is critical in the assessment of likely impacts on the wetland, which typically could arise from groundwater abstraction, drainage or agricultural practice. The awareness of the significance of groundwater to fens was increased with implementation of the EU Water Framework Directive, under which fens classify as groundwater dependent terrestrial ecosystems (GDTE) and must be included in River Basin Management plans nationwide. Wetland studies have a long history; however a quantitative assessment of eco-hydrological interactions within them is difficult and hardly exists in Ireland. In this study a multidisciplinary approach was adopted and the ecohydrology of the fen of Pollardstown, Co. Kildare was examined. This investigation was focused at the fen margin, where groundwater discharges from the surrounding aquifer as springs and seepages, and creates an interesting habitat that combines a mixture of rare plants and animal species, many of which are protected under the EU Habitats Directive. The specific interest of the study was set on the conservation requirements of Vertigo geyeri snail and the habitat it lives in. As such, the investigation was focused on selected areas of the fen margin where the snail was known to occur and that were considered to be potentially threatened by a combination of natural and human-induced factors.
Keywords: Civil Engineering, Ph.D.; Ph.D. Trinity College Dublin